HBM4EU chromates study: usefulness of measurement of blood chromium levels in the assessment of occupational Cr(VI) exposure - Ndaw, Sophie (2022)
Occupational exposures to hexavalent chromium (Cr(VI)) can occur in welding, hot working stainless steel processing, chrome plating, spray painting, and coating activities. Recently, within the human biomonitoring for Europe initiative (HBM4EU), a study was performed to assess the suitability of different biomarkers to assess the exposure to Cr(VI) in various job tasks. Blood-based biomarkers may prove useful when more specific information on systemic and intracellular bioavailability is necessary. To this aim, concentrations of Cr in red blood cells (RBC-Cr) and in plasma (P–Cr) were analyzed in 345 Cr(VI) exposed workers and 175 controls to understand how these biomarkers may be affected by variable levels of exposure and job procedures. Compared to controls, significantly higher RBC-Cr levels were observed in both plating and paint application workers, but not in welders, while all the 3 groups had significantly greater P–Cr concentrations. RBC-Cr and P–Cr in chrome platers showed a high correlation with Cr(VI) in inhalable dust, outside respiratory protective equipment (RPE), while such correlation could not be determined in welders. In platers, the use of RPE had a significant impact on the relationship between blood biomarkers and Cr(VI) in inhalable and respirable dust. Low correlations between P–Cr and RBC-Cr may reflect a difference in kinetics. This study showed that Cr-blood-based biomarkers can provide information on how workplace exposure translates into systemic availability of Cr(III) (extracellular, P–Cr) and Cr(VI) (intracellular, RBC-Cr). Further studies are needed to fully appreciate their use in an occupational health and safety context.